2004
DOI: 10.1111/j.1365-2044.2004.03571.x
|View full text |Cite
|
Sign up to set email alerts
|

Continuous haemodynamic monitoring using transoesophageal Doppler during acute normovolaemic haemodilution in patients with coronary artery disease

Abstract: SummaryTransoesophageal Doppler monitoring allows non-invasive assessment of stroke volume. We studied haemodynamic changes during acute normovolemic haemodilution (ANH) in anaesthetised patients with coronary artery disease. Twenty patients were randomly assigned to either ANH or a control group. During ANH, a mean (SD) blood volume of 15.3 (3.4) ml.kg )1 was withdrawn decreasing systemic oxygen delivery from 12.7 (3.3) to 9.3 (1.8) ml.kg.min )1 (p < 0.001).In the control group, haemodynamic data remained unc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 49 publications
1
7
0
1
Order By: Relevance
“…This may follow both acute or chronic opioid intake. Acutely, it usually manifests as a part of a postoperative ileus that itself may be attributed to surgical stress, or to alterations in fluid and electrolyte balance [1]. In…”
Section: Peripheral Opioid Antagonismmentioning
confidence: 99%
See 1 more Smart Citation
“…This may follow both acute or chronic opioid intake. Acutely, it usually manifests as a part of a postoperative ileus that itself may be attributed to surgical stress, or to alterations in fluid and electrolyte balance [1]. In…”
Section: Peripheral Opioid Antagonismmentioning
confidence: 99%
“…A quick scan through the contents pages from 2004 reveals an eclectic mixture of areas of patient care and basic science where anaesthetists have made, and continue to make, their mark. In our own specialist fields, we have designed, developed and tested new technologies to improve safety and quality of care [1,2]. We have become more adept at managing difficult, life-threatening airway problems [3,4].…”
mentioning
confidence: 99%
“…34 In patients scheduled for CABG surgery, several studies demonstrated that moderate ANH (target hematocrit value 27-33%) is well tolerated, provided that determinant of systemic and myocardial oxygen demand are well controlled. [35][36][37] In these patients, cardiac medication, especially β-blockers, was maintained until the day of surgery and ANH was performed under anesthesia to avoid the increase in heart rate usually observed in awake patients in these circumstances. 11 However, any increase in myocardial O 2 demand in these conditions could be associated with the development of myocardial ischemia and cardiac dysfunction.…”
Section: Anh and Coronary Artery Diseasementioning
confidence: 99%
“…A study demonstrated that ANH to a mean hemoglobin value of 8.6 g/dL was well tolerated in anesthetized patients with coronary artery disease who were receiving beta-blockers. These patients presented no ECG abnormalities or hemodynamic instability (Licker et al, 2004). A recent study comparing transfusion strategies in 512 patients, submitted to cardiac surgery, found that a restrictive strategy, defined as a transfusion performed when the hematocrit reached values of  24%, was as safe as the liberal strategy, defined as hematocrit  30%.…”
Section: Heart Tolerance To Acute Anemiamentioning
confidence: 99%